Dampak Penerapan Sistem Verifikasi Legalitas Kayu Terhadap Kelestarian Produksi Kayu Hutan Rakyat Di Kabupaten Gunungkidul, Di. Yogyakarta - SYOFII, Achmad ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The implementation of Timber Legality Verification System (SVLK) in community forests is expected to be beneficial at economic issues such as market access expansion and premium price incentive to Community Forest Management Unit (Unit Manajemen Hutan Rakyat - UMHR). The aims of the study are to: (1) figure out the changes in demand and prices of timber after the UMHR acquires timber legality certificate, and (2) determine the demand effect on timber production sustainability in community forest after the UMHR acquires timber legality certificate. The research was conducted using qualitative and quantitative approaches in Dengok Village, Playen Subdistrict, Gunungkidul Regency, Yogyakarta Special Region. The technique of data and information collection are: documentation, interviews with the respondents and key informants to obtain timber utilization and prices, as well as a survey of the stands in the community forest of the UMHR in Dengok Village. Data analysis used in this study is the method of before and after comparisons. The mean of wood demand to the UMHR in Dengok Village before timber legality certification is 319 per year or 18.404 m³ and after the issued is 1 (one) or 0.184 m³ teak logs, meaning there is a decrease in the average demand per year of 318 or 18.220 m³. Timber prices increased after the timber legality certification is issued as much as 3 percents for OGD quality and 4 percents for OD quality of teak logs. Utilization of community forest wood in Dengok Village before and after the certification does not exceed the Annual Allowable Cut (AAC) or there is no over cutting. Thus the sustainability of timber production in community forest of Dengok Village is well maintained. The legalization of Timber Legality Verification System does not affect the sustainability of timber production in Dengok Village Community Forest.